Perceived Stress Mediating the Association Between Mindfulness and Resilience Among Registered Nurses - Chen SH; Chen PJ; Lee CH; Wu YP; Ahorsu DK; Griffiths MD; Lin CY (Psychology Research and Behavior Management, 2023)
Shun-Hua Chen,1 Po-Jen Chen,2 Chiu-Hsiang Lee,3,4 Yu-Ping Wu,3,4 Daniel Kwasi Ahorsu,5,6 Mark D Griffiths,7 Chung-Ying Lin8 1School of Nursing, Fooyin University, Kaohsiung, 83102, Taiwan; 2Department of Medical Research, E-Da Hospital, I-Shou University, Kaohsiung, 824005, Taiwan; 3Department of Nursing, Chung Shan Medical University, Taichung, Taiwan; 4Department of Nursing, Chung Shan Medical University Hospital, Taichung, Taiwan; 5Mental Health Research Centre, the Hong Kong Polytechnic University, Hung Hom, Hong Kong; 6Department of Special Education and Counselling, the Education University of Hong Kong, Tai Po, Hong Kong; 7International Gaming Research Unit, Psychology Department, Nottingham Trent University, Nottingham, UK; 8Institute of Allied Health Sciences, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Chiu-Hsiang Lee, Department of Nursing, Chung Shan Medical University, Department of Nursing, Chung Shan Medical University Hospital, 1253F, Jengshin Hall, Taichung, 402, Taiwan, Tel +886-4-24730022 ext. 12216, Email csha528@gmail.com Daniel Kwasi Ahorsu, Department of Special Education and Counselling, The Education University of Hong Kong, B4-1/F-13, Tai Po, Hong Kong, Email daniel.ahorsu@connect.polyu.hkPurpose: Resilience continues to be an important concept in the nursing profession due to its significant role in personal healthcare, patients’ healthcare, and leadership. The present study examined the mediating role of perceived stress in the association between mindfulness and resilience among registered nurses in order to understand their importance among those in the Taiwanese nursing profession.Materials and Methods: Between October and November 2021, a total of 816 registered nurses participated in a cross-sectional survey including psychometric measures assessing perceived stress (Chinese Perceived Stress Scale-10), mindfulness (Chinese Mindful Attention Awareness Scale), and resilience (Chinese Questionnaire of Resilience).Results: Results indicated that perceived stress mediated the association between mindfulness and resilience (standardized coefficient = 0.251, p< 0.001), although there was no significant association between mindfulness and resilience (standardized coefficient = 0.042, p=0.16). This suggests that perceived stress may function as both distress and eustress because mindfulness was not directly associated with resilience but indirectly via perceived stress.Conclusion: Nurses and their administrators should focus on different ways of coping with stress so that they become more resilient in facing other stressors. Future studies may be conducted to examine the mediating role of perceived stress in the association between other coping strategies and resilience among registered nurses.Keywords: coping, healthcare, Taiwan, cross-sectional survey, mediation analysis, mindfulness, resilience